Subject-specific finite-element modeling of normal aortic valve biomechanics from 3D+t TEE images - Labrosse, Michel; Beller, Carsten J.; Boodhwani, Munir; Hudson, Christopher; Sohmer, Benjamin (Medical image analysis, 2015)
In the past decades, developments in transesophageal echocardiography (TEE) have opened new horizons in reconstructive surgery of the aortic valve (AV), whereby corrections are made to normalize the geometry and function of the valve, and effectively treat leaks. To the best of our knowledge, we propose the first integrated framework to process subject-specific 3D+t TEE AV data, determine age-matched material properties for the aortic and leaflet tissues, build a finite element model of the unpressurized AV, and simulate the AV function throughout a cardiac cycle.
Available online 15 November 2014
Gesehen am 05.06.2020